Rock Subcultures versus Pop Music: Italian Pop Music at the Czechoslovak Bratislavská lýra Festival - Kajanová, Yvetta (Scenari, 2024)
Drawing on critical reviews in the Czech and Slovak press regarding the Bratislavská lýra [Bratislava Lyre] pop music festival, held annually in Bratislava from 1966 to 1998, the author examines the conformist, ambivalent, and antagonistic relationships between pop music and rock subcultures, while also giving attention to the commentaries about Italian participants, such as Rita Pavone, Drupi, Nino Rota, Toto Cutugno, Aldo Riva, Sabrina, and the Al Bano & Romina Power duo. Besides the substantial influence of rock subcultures – in particular hard rock, New Wave, progressive rock, and heavy metal – which brought changes to instrumentation, image, clothing, and stage presentation, other genres (e.g. reggae and funk) also steered the developmental directions of this festival. Whilst in its first stage (1966–77), the Bratislavská lýra mainly featured a Sanremo-like bel canto style of pop music with orchestral accompaniment, in the subsequent period (1977–98) contestants began incorporating rock show attributes. Cantilena-versus-rhythm and orchestra-versus-rock band polemics accompanied the event until its final year: on the one hand, there were endeavours to transform it from a pop music show into a presentation of rock clubs (in 1990–93) and, on the other, efforts to restore the original cantilena-orchestra model (in 1996–98). Ultimately, the antagonistic competition between rock subcultures and pop music played a decisive role in the demise of the Bratislavská lýra in 1998.